Economic diversification is a sustainable development model to confront the non-renewable energy resources in Algeria. - Meddahi, Mohamed (Dirassat Journal Economic Issue, 2022)
This research paper aims to show the extent of the contribution of energy diversification through investment in renewable energies to achieving economic development, and the extent of reliance on energy diversification within the economic diversification strategy in Algeria. , as it was relied on the inductive approach that depends on description and analysis, and the study showed that Algeria is one of the countries that sought to develop clean energy strategies to advance its economy, especially since its current economic system is based on its fossil energy sources with a percentage of nearly 97% of Algeria’s income, and this makes The national economy is a dependency economy.